The challenge of measuring IL-33 in serum using commercial ELISA: lessons from asthma - Ketelaar, M.E.; Nawijn, Martijn C.; Shaw, Dominick E.; Koppelman, Gerard H.; Sayers, Ian (Wiley, 2016)
Background Interleukin-33 (IL-33) has been subject of extensive study in the context of inflammatory disorders, particularly in asthma. Many human biological samples, including serum, have been used to determine the protein levels of IL-33, aiming to investigate its involvement in asthma. Reliable methods are required to study the association of IL-33 with disease, especially considering the complex nature of serum samples. Objective We evaluated four IL-33 ELISA kits, aiming to determine a robust and reproducible approach to quantifying IL-33 in human serum from asthma patients. Methods IL-33 levels were investigated in serum of well-defined asthma patients by the Quantikine, DuoSet (both R&D systems), ADI-900-201 (Enzo Life Sciences), and SKR038 (GenWay Biotech Inc San Diego USA) immunoassays, as well as spiking experiments were performed using recombinant IL-33 and its soluble receptor IL-1RL1-a. Results We show that 1) IL-33 is difficult to detect by ELISA in human serum, due to lack of sensitivity and specificity of currently available assays; 2) human serum interferes with IL-33 quantification, in part through IL-1RL1-a; and 3) using non-serum certified kits may lead to spurious findings. Conclusion and Clinical Relevance If IL-33 is to be studied in the serum of asthma patients and other diseases, a more sensitive and specific assay method is required, which will be vital for further understanding and targeting of the IL-33/IL-1RL1 axis in human disease.